PROBLEMATIKA PEDAGANG BUAH KAKI LIMA DI KOTA PALANGKA RAYA - Sofyan Hakim; Sali Sali; Akhmad Alfauji (AL-QARDH, 2018)
The problem of fruit street vendors is because they open their trade use the part of fruit street or sidewalk and other places for public’s importance that not for the trade and the place that not belong to them that’s way the street vendors become a difficult problem to solve well.  The research problem are 1)  What is the problem faced by fruiterer when trading in Palangka Raya City?  2) How does the view from the fruiterer about the government’s role in helping the fruiterer when trading?.This research used field research and used qualitative approach.  The object of this research was the problem faced by fruiterers at Palangka Raya City.  The subject of this research was the fruiterers that trade at sidewalk.  The data collection technique used interview, observation and documentation.The result of this research shows that 1) There is no special place for street vendors that make them difficult to trading.  2) The street vendors hopefully for government to gave them a special place for trade especially for the fruiterers.